The metabolic-immune interface of obesity in Covid-19: a role for angiotensin ii and inflammatory cytokines - Rodrigues, Cíntia Maria; Santos, Juliane Duarte; Garcia, Bruna Carolina Chaves; Ottoni, Marcelo Henrique Fernandes; Costa, Karine Beatriz; Costa, Marina Luiza Baêta; Figueiredo, Vívian Gonzalez; Macedo, Daniel; Bretas de Oliveira, Danilo; Rocha Vieira, Etel; Cárnio, Evelin Capellari (Frontiers in Immunology, 2026)
BackgroundObesity is a major risk factor for severe COVID-19, partly explained by chronic systemic low-grade inflammation and renin-angiotensin-aldosterone system (RAAS) dysregulation.ObjectivesTo investigate the relationship between obesity and COVID-19 severity by measuring plasma angiotensin II (Ang II) and pro and anti-inflammatory cytokines across BMI categories.MethodsIn a cross-sectional cohort of 142 adults (Lean and Obese), including mild and severe COVID-19 cases and matched uninfected controls. Plasma Ang II, IL-1β, IL-6, IL-10, and TNF were quantified by ELISA. Associations with BMI and clinical severity were assessed using ANOVA and correlation analyses.ResultsObese patients showed elevated Ang II, IL-1β, IL-6, and TNF, alongside reduced IL-10, compared to lean individuals and controls. Ang II positively correlated with BMI. Severe cases showed elevated neutrophil-to-lymphocyte ratios and greater need for ventilatory support requirements. Notably, mortality occurred exclusively among obese patients.ConclusionObesity exacerbates COVID-19 severity through RAAS imbalance and, amplified inflammatory responses. Ang II and pro-inflammatory cytokines may serve as early predictive biomarkers of disease progression in obese individuals, highlighting the metabolic-immune interface as a critical determinant of COVID-19 outcomes.